2015
DOI: 10.1016/j.cplett.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical prediction on huge hole and electron mobilities of 6,6,18-graphdiyne nanoribbons

Abstract: Two-dimensional 6,6,18-graphdiyne and the corresponding one-dimensional nanoribbons are investigated using crystal orbital method. Based on HSE06 functional, the one-dimensional confinement increases the band gaps. With band gaps larger than 0.4 eV, thirty-three 6,6,18-graphdiyne nanoribbons have larger majority carrier mobilities at room temperature than the highest value of armchair graphene nanoribbons. Unlike γ-graphdiyne, 6,6,18-graphdiyne nanoribbons have both huge hole and electron mobilities, depending… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It was demonstrated by both experimental investigation and theoretical studies that, as a novel carbon allotrope, GDY is a semiconductor. Using the Boltzmann transport equation based relaxation time approximation, as well as DFT calculations, the carrier mobility of GDY-NRs and GDY sheets have been studied through longitudinal acoustic phonon scattering. ,,, The hole and electron mobilities of GDYs with a single layer were theoretically predicted to be around 2 × 10 4 and 2 × 10 5 cm 2 V –1 s –1 at 300 K, respectively . The electron mobility of GDY-NRs at room temperature is apparently larger than its hole mobility and can reach the order of magnitudes in 10 5 cm 2 V –1 s –1 .…”
Section: Properties and Potential Application Of Gdymentioning
confidence: 97%
“…It was demonstrated by both experimental investigation and theoretical studies that, as a novel carbon allotrope, GDY is a semiconductor. Using the Boltzmann transport equation based relaxation time approximation, as well as DFT calculations, the carrier mobility of GDY-NRs and GDY sheets have been studied through longitudinal acoustic phonon scattering. ,,, The hole and electron mobilities of GDYs with a single layer were theoretically predicted to be around 2 × 10 4 and 2 × 10 5 cm 2 V –1 s –1 at 300 K, respectively . The electron mobility of GDY-NRs at room temperature is apparently larger than its hole mobility and can reach the order of magnitudes in 10 5 cm 2 V –1 s –1 .…”
Section: Properties and Potential Application Of Gdymentioning
confidence: 97%
“…52 The electronic properties of GYNRs and GDYNRs with different widths and edges have been investigated. [53][54][55][56][57][58][59][60][61][62][63] Studies have shown that the mobility of GDYNRs with two edge configurations increases with increasing nanoribbon width. The effective electron (hole) mass of AGDYNRs is smaller than that of ZGDYNRs (Fig.…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…Due to the weak bonding of carbon–carbon sp–sp 2 , GDYNRs and GYNRs (γ-GY, α-GY, β-GY, 6,6,12-GY, β-GDY and δ-GDY) can be obtained by opening the carbon–carbon bond and shearing two-dimensional infinite GDY nanosheets in an orthogonal way. 57–62 As shown in Fig. 2, the suspended edge bonds are all passivated by hydrogen atoms.…”
Section: Introduction To Gynrs and Gdynrsmentioning
confidence: 97%
See 1 more Smart Citation